The Precautionary Principle Meets the Hill Criteria of Causation. Issue 1 (2nd January 2019) - Steel, Daniel; Yu, Jessica
ABSTRACT: This article examines the relationship between the precautionary principle and the well-known Hill criteria of causation. Some have charged that the Hill criteria are anti-precautionary because they are strongly inclined towards false negatives in multi-causal contexts typical of environmental and public health issues. However, we argue that without guidance on how to interpret and weight the criteria, no such claims can be supported. Using a case study of tuberculosis among South African goldmine workers, we consider the implications of different weightings of the Hill criteria and how they might be appropriate depending on the stakes of error.